Penerjemahan Soneta “If Thou Must Love Me” Karya Elizabeth Barrett Browning dari Bahasa Inggris ke Bahasa Indonesia: Terjemahan Beranotasi - Wulandari, Tilly (Kementerian Sekretariat Negara Republik Indonesia, 2021)
The sonnet “If Thou Must Love Me” by Elizabeth Barrett Browning is one of the sonnets from the Victorian era which is part of a collection of sonnets entitled Sonnets from the Portuguese which was published in 1850. The author performs an annotated translation of this sonnet to explain each word choice and meaning in the translation. The author translated this sonnet using the translation technique popularized by Molina and Albir to find out the exact meaning of this Old English sonnet. The result of this translation shows that this sonnet uses the Petrarchan pattern, but with a slightly different part of the sestet from the general Petrarchan pattern, namely cdcdcd. The author also finds that this sonnet does not only contain the meaning of love, but also fears and hopes. In addition, the translation technique that is widely used in the translation of this sonnet is the variation technique followed by calque, common equivalent, compensation, reduction, modulation, and transposition. Keywords: Sonnet, Translating, Petrarchan.